Human hand impedance characteristics during maintained posture - Tsuji, Toshio; Morasso, Pietro G.; Goto, Kazuhiro; Ito, Koji (Biological cybernetics, 1995)
The present paper examines human hand impedance characteristics, including inertia and viscosity as well as stiffness, in multi-joint arm movements. While a subject maintains a given hand location, small external disturbances are applied to his hand by a manipulandum. The corresponding force-displacement vectors are measured and sampled over time in order to estimate the hand impedance by means of a second-order linear model. The experimental results in different subjects and hand locations are summarized as follows: (1) the estimated inertia matrices of the human hand well agrees with computed values using a two-joint arm model, (2) spatial variations of the stiffness ellipses are consistent with the experimental results of Mussa-Ivaldi et al. (1985), (3) hand stiffness and viscosity increase with the grip force of the subject, and (4) viscosity and stiffness ellipses tend to have similar orientation. The accuracy of the impedance estimation method is validated with a mechanical spring-mass system with known parameters.